Numerical Computation of a Water-Quality Model with Advection-Diffusion-Reaction Equation Using an Upwind Implicit Scheme: Piyada Phosri, Nopparat Phochai - Team, Support (Thai Journal of Mathematics, 2021)
In this research, numerical water-quality model calculations are proposed within a uniform flow stream. The governing equation, which is an equation of advection-diffusion-reaction, is approximated by using a technique of finite differences. The upwind-implicit scheme is used at all times on an uniform flow stream to approximate the pollutant concentration at each point. The accuracy of the proposed computing technique is compared with the analytical, and the examples show approximate solutions.